KEKASARAN PERMUKAAN RESIN KOMPOSIT NANOFILLER SETELAH PERENDAMAN ALAM AIR SUNGAI DAN AIR PDAM - M. Hasriandy Candra Basri; Isyana Erlita; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2017)
ABSTRACTBackground :One of composite resin kinds is often used for tooth restoration, it is nanofilled composite resin. Nanofilled composite resin is a restoration material containing nano size filler particle, so that it can repair the physical characteristic of composite such as reducing the surface roughness. People in Barito Kuala especially in Desa Anjir Pasar, besides using tap water, they also still use water from river for daily use. The water of river in Desa Anjir Pasar has acid characteristic with Ph range 3-5. An acidic environment causes surface roughness of nanofilled composite resin which allow the secunder caries.Purpose : The aim of this research was to know the difference in surface roughness of nanofilled composite resin after being immersed in river water, tap water, and sterile aquades. Method :This research was a true experimental research with post test only and control group design, used nanofilled composite resin disc samples with diameter of 10 mm and 2 mm thick divided into 3 groups of treatment. Each group was immersed in sterile aquades (as control group), tap water, and river water with acid Ph for 8 days (equals to 3 years of exposure), then the surface roughness was measured using surface roughness measurement. Result : Data was tested using parametric analysis one way anova 95% ( = 0,05) and it obtained p = 0,000 (p = < 0,05). Based on the result it can be concluded that there was significant difference in surface roughness on nanofilled composite resin which had been immersed in each water sample for 8 days. Conclusion : Nanofilled resin composite immersed in river water had higher mean value of surface roughness compared to immersion in sterile aquades and tap water.Keywords: Resin Nanofilled Composite, River Water, Tap Water, Surface Roughness